Diversity of MHC IIB genes and parasitism in hybrids of evolutionarily divergent cyprinoid species indicate heterosis advantage - Šimková, Andrea; Gettová, Lenka; Civáňová, Kristína; Seifertová, Mária; Janáč, Michal; Vetešník, Lukáš (Scientific reports, 2021)
The genes of the major histocompatibility complex (MHC) are an essential component of the vertebrate immune system and MHC genotypes may determine individual susceptibility to parasite infection. In the wild, selection that favors MHC variability can create situations in which interspecies hybrids experience a survival advantage. In a wild system of two naturally hybridizing leuciscid fish, we assessed MHC IIB genetic variability and its potential relationships to hosts' ectoparasite communities. High proportions of MHC alleles and parasites were species-specific. Strong positive selection at specific MHC codons was detected in both species and hybrids. MHC allele expression in hybrids was slightly biased towards the maternal species. Controlling for a strong seasonal effect on parasite communities, we found no clear associations between host-specific parasites and MHC alleles or MHC supertypes. Hybrids shared more MHC alleles with the more MHC-diverse parental species, but expressed intermediate numbers of MHC alleles and positively selected sites. Hybrids carried significantly fewer ectoparasites than either parent species, suggesting a hybrid advantage via potential heterosis.
Keywords: alely; lineární modely; Crosses, Genetic; Hybridization, Genetic; Biological Evolution; Models, Biological; Alleles; zvířata; hybridní efekt; hybridizace genetická; křížení genetické; Major Histocompatibility Complex; biologická evoluce; Linear Models; biologické modely; Bayesova věta; hlavní histokompatibilní komplex; Hybrid Vigor; Animals; Bayes Theorem; selekce (genetika); Selection, Genetic; Cyprinidae